Answer:
y=x+3
Explanation:
Start with the slope equation
![(y_(2) -y_(1) )/(x_(2) -x_(1) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/s06yw3rxucupe255cg3q6k66khkazgdgo1.png)
Since the first point is actually further along the x-axis that x-value becomes
and its corresponding y-value is
![y_(2)](https://img.qammunity.org/2022/formulas/mathematics/college/bmz61eqncfplw06sozzz8czebdgjabtcak.png)
=
![(1)/(1)](https://img.qammunity.org/2022/formulas/history/high-school/fcpnhe59bx8vpzdfh8cjvo0f54geffhvj3.png)
The slope for the equation is just one so now find the y-intercept by rearranging the slope-intercept equation.
y=mx+b
y-mx=b
Now Substitute either point in to find b
9-1(6)=b
9-6=b
b=3
Your y-intercept is 3 so now we can write the slope-intercept equation for the two points:
y=x+3